Til death do us part? The critical value of long-term marine mammal studies - Kraus, Scott D. (Frontiers in Marine Science, 2025)
Long term studies in ecology and biology have been essential for addressing significant evolutionary and ecological questions. Long term marine mammal studies face different challenges, but are proving critical to ocean policy. New technologies combined with long term marine mammal studies provide important information on trends in population biology, anthropogenic stressors, climate change, and oceanographic regime shifts.